2023
DOI: 10.1002/vnl.22026
|View full text |Cite
|
Sign up to set email alerts
|

3Dpolymer composite filament development from post‐consumer polypropylene and disposable chopstick fillers

Abstract: This study focused on the development of three‐dimensional (3D) polymer composite filament made of disposable chopstick (DC) and post‐consumer polypropylene (PPP). The PPP/DC composite parts were printed via fused filament fabrication (FFF) process. The effect of the printing temperature and different DC fiber content on the properties of the 3D printed parts were investigated. The printing temperature of 200–220°C was suitable for these filaments because the printing temperature did not show any thermal degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…To overcome this issue, the printing temperature must be increased as reported earlier. Similar findings were also observed by Tan et al 14 and Ariel Leong et al 16 who found that filament with higher fiber content were difficult to print uniformly due to the highly distracted melt flow caused by the presence of fiber.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To overcome this issue, the printing temperature must be increased as reported earlier. Similar findings were also observed by Tan et al 14 and Ariel Leong et al 16 who found that filament with higher fiber content were difficult to print uniformly due to the highly distracted melt flow caused by the presence of fiber.…”
Section: Resultssupporting
confidence: 87%
“…As a result, the warping effect of the printed part with rPP/CHF filament containing higher CHF content is less pronounced. In addition, Tan et al 14 reported a significant reduction in warpage of printed parts with rPP composite filament when adding fiber made from disposable chopstick. They also confirmed that the presence of natural fiber has a positive effect on the warping issue when printing rPP‐based materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight loss from rePP between 410 and 500 C was predominantly due to the thermal degradation of the C C bonds in its main chain. 43 The residual mass of 1.88% at 700 C was primarily due to residual carbon generated during the hightemperature degradation of rePP. On the other hand, the thermal weight loss curves of the rePP/WF composites showed two thermal degradation plateaus (Figure 9A).…”
Section: Tg Analysismentioning
confidence: 99%
“…Each filler comes with specific recycling challenges depending on its composition and origin. For example, (organic) wood flour obtained from pulverised disposable chopsticks [198] and (inorganic) glass fibres reclaimed from wind turbine blades [17] are likely to follow different recycling procedures and require different compounding strategies for producing printable filaments. As a result, generalising is not possible.…”
Section: Fillersmentioning
confidence: 99%